A review of the evidence on hate crime and prejudice: report for the independent advisory group on hate crime, prejudice and community cohesion - McBride, Maureen (Report, 2016)
The SCCJR was commissioned to explore the nature of evidence on hate crime in Scotland in order to support the work of the Advisory Group on Hate Crime and Prejudice. This report summarises key sources of information as well as addresses some issues around the definition and understanding of hate crime as a social phenomenon. In addition, as part of this project, a series of key stakeholders comprising national and local organisations were surveyed to explore organisational data collection, usage and perceived gaps in information.